2010
DOI: 10.1603/me09072
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phlebotomine Sand Flies (Diptera: Psychodidae) in a Primary Forest-Crop Interface, Salta, Argentina

Abstract: Disordered urbanization and deforestation are the main activities proposed as causal factors of re-emergence of American cutaneous leishmaniasis caused by Leishmania braziliensis. The purpose of this work was to investigate, in the hyperendemic area of Argentina, the distribution of Phlebotomine sand flies at the modified primary vegetation-crop interface, as one of the potential sites where the effects of changing landscape on sand fly populations may be manifested. Twenty samplings were made between June 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 19 publications
3
47
0
4
Order By: Relevance
“…La ausencia de una estacionalidad acentuada de las variables de precipitación y temperatura, con la presencia de periodos largos (ocho meses) de poca precipitación mensual (149 a 220 mm) y periodos cortos (cuatro meses) de alta precipitación mensual (240 a 320 mm), favorece la persistencia de las poblaciones de estos tres flebotomínos en la zona de muestreo, siendo la precipitación una variable macroclimática aparentemente importante para la dinámica de transmisión de la leishmaniasis (20).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La ausencia de una estacionalidad acentuada de las variables de precipitación y temperatura, con la presencia de periodos largos (ocho meses) de poca precipitación mensual (149 a 220 mm) y periodos cortos (cuatro meses) de alta precipitación mensual (240 a 320 mm), favorece la persistencia de las poblaciones de estos tres flebotomínos en la zona de muestreo, siendo la precipitación una variable macroclimática aparentemente importante para la dinámica de transmisión de la leishmaniasis (20).…”
Section: Discussionunclassified
“…Esta aproximación espacio-temporal de la infección natural permite reconocer patrones clave en el riesgo y la vulnerabilidad a la infección por agentes patógenos en una zona geográfica donde el vector incriminado o potencial está presente (18)(19)(20), y hacer una valoración rápida de los focos de transmisión y las zonas de riesgo.…”
unclassified
“…Recent work by Quintana and Salomon in Argentina showed a strong negative correlation between rainfall and the abundance of sand flies. 17 Unfortunately, most published studies only involve univariate analysis of climatic factors and thus take the risk of describing synchronous but possibly independent seasonal phenomenon. The advantage of ARIMA models, like the one used in this study, was to remove this seasonal component and to perform a multivariate analysis that confirms, with a similar 2-month lag, the negative correlation between rainfall and the number of infections.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant species of Leishmania responsible for ATL has been L. (V.) braziliensis. 6,7 We found a high density of these potential vectors in the exposure area, 50-fold higher than previous captures in the same region, 24 which may partially explain the finding that all exposed individuals became infected. The natural infection of Lu.…”
Section: Discussionmentioning
confidence: 55%
“…Proximity to forest edge (or forest fringe) has been found to be positively associated with vector density caused by favorable conditions for vector breeding, and is a known risk factor for infection. 24 Findings from our study of this outbreak highlight the intensity of the exposure and risk manifested by the fact that all of the hunters became infected despite a short exposure period of several hours. Multiple studies have reported transmission events in rural and jungle areas associated with labor, recreational, and military activities.…”
Section: Discussionmentioning
confidence: 67%